Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian (Studi Kasus Mahasiswi UIN Raden Intan Lampung) - Lustika, Clarisa Nurul; Yuningsih, Mela; Novianto, Sevira Gabila; Aftika, Sonia; Helmi, Syifa (Jurnal Manajemen DIVERSIFIKASI, 2021)
This study aims to examine the effect of brand image and product quality on purchasing decisions (a case study of UIN RADEN INTAN LAMPUNG student. This type of research is a quantitative research that is causal comparative (causal comparative reasarch), namely a causal relationship between two or more variables. This research is a student of UIN RADEN INTAN LAMPUNG and obtained a sample of 100 respondents. Data collection techniques in this study using a questionnaire distributed online via google form. Based on the results of the analysis of the t test it can be explained that brand image and product quality partially affect positive and significant towards purchasing decisions, where each independent variable (brand image and product quality) has a value of t sig <0.05. Based on the results of the analysis of the F test, it can be explained that brand image and product quality simultaneously have a positive and significant effect. on purchasing decisions, where the value of F sig is 0.000 <0.05. For further research, it is hoped that it can examine more deeply about the title and add other variables in it.